2021
DOI: 10.4238/gmr18754
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Implications of <i>GSTM1</i>, <i>GSTT1</i>, and <i>GSTP1</i> polymorphisms for susceptibility to chronic lymphocytic leukemia

Abstract: possible genetic associations between GSTM1/GSTT1 deletion and GSTP1 rs1695 polymorphisms with CLL risk in a central Brazilian population. For GSTM1/GSTT1 deletion polymorphism, genotyping was performed with multiplex real-time PCR (qPCR), and for GSTP1 rs1695 polymorphism, PCR-RFLP was used. The GSTM1 null genotype presented a trend towards CLL risk. However, GSTT1 deletion polymorphism presented a protective effect for CLL (OR=0.26, p<0.005).The GSTP1 rs1695 was not associated with disease susceptibility. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Scientific reports regarding glutathione S-transferases genetic in the leukemia context of Brazilian population are few, however some examples chase for GSTM1 and GSTT1 influence in cancer. Cancer development is linked to an imbalance between cellular detoxification enzymatic system and exposure to carcinogenic agents, where glutathione S-transferases system present an essential role (Reis et al 2021). A classical Brazilian report showed that GSTM1 and GSTT1-null frequency between different Brazilian ethnicities are linked to carcinogenesis (Arruda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientific reports regarding glutathione S-transferases genetic in the leukemia context of Brazilian population are few, however some examples chase for GSTM1 and GSTT1 influence in cancer. Cancer development is linked to an imbalance between cellular detoxification enzymatic system and exposure to carcinogenic agents, where glutathione S-transferases system present an essential role (Reis et al 2021). A classical Brazilian report showed that GSTM1 and GSTT1-null frequency between different Brazilian ethnicities are linked to carcinogenesis (Arruda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A report demonstrated that GSTM1 and GSTT1 null genotypes were higher in cases than in controls and there was evidence of a trend in increasing risk with the number of putative "high-risk" alleles of the GST family carried (Yuille et al 2002;Lordelo et al 2012). A recent data suggest that GSTT1 positive genotype may represent a protective effect over CLL, however highlighting bias because ethnic heterogeneity in Brazilian population (Reis et al, 2021). A Russiona study demonstrated that the combination of unfavorable polymorphic CYP1A1 variants and GSTM1 null genotype was found more frequently in B-CLL patients relative to controls (Gra et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation